The Effect of Lonicera japonica on LPS-Stimulated B-Cell Functions. Issue 2 (2nd April 2016) - Curry, Michael; Brooks, Austin; Bruns, Heather A.
ABSTRACT: Lonicera japonica has been shown to have antibacterial, antiviral, and anti-inflammatory properties. Given these properties, varying preparations of L. japonica are being used increasingly as immune enhancers. However, isolated compounds from L. japonica can inhibit lymphocyte functions, which would oppose the ability of L. japonica to serve as an immune enhancer. Prior studies in our laboratory demonstrated that an herbal powder extracted from the leaves of L. japonica inhibits T lymphocyte proliferation and survival. Because both T- and B-cell functions and interactions are required for effective immune responses, the effect of L. japonica on LPS-stimulated B-lymphocyte functions was assessed. Our data demonstrate that while total and IgM+ B cells are not largely diminished as a result of L. japonica treatment, IgM production was decreased, potentially as a consequence of suppressed proliferation.